The Development of Reading Skills Through Gamification-Based Learning Combined with Citta Bhāvanā for Prathom Suksa 2 Students at Anuban Nakhon Champasri School, Maha Sarakham Province - Seelapang, Kannika; Sribunrueang, Pacharakit; Khraiboot, Adcharaporn (Journal of Buddhist Education and Research (JBER), 2026)
This research aimed to: (1) develop a Thai reading skill development lesson plan using gamification-based learning integrated with Citta Bhāvanā, targeting the efficiency criteria of 80/80, (2) compare learning achievements in Thai reading skills before and after implementing the gamification and Citta Bhāvanā-based instruction, and (3) examine students’ satisfaction toward the learning approach. The target group consisted of 22 Prathom Suksa 2/2 students from Anuban Nakhon Champasri School, Maha Sarakham Province. The research instruments included: (1) the Thai reading skill development lesson plans based on gamification and Citta Bhāvanā, (2) a learning achievement test, and (3) a satisfaction questionnaire. Data were analyzed using basic statistics: mean, standard deviation (S.D.), and the dependent t-test. The research results were as follows: 1) The Thai reading skill development lesson plan, using gamification-based learning combined with Citta Bhāvanā for Prathom Suksa 2/2 students, achieved an efficiency of 88.77/88.86, which is higher than the specified criterion of 80/80. 2) Students’ learning achievement in Thai reading through gamification-based learning integrated with Citta Bhāvanā showed that the mean pre-test and post-test scores were 9.68 and 17.05, respectively. A comparison of the scores revealed that the post-test mean was significantly higher than the pre-test mean at the .05 level of statistical significance. 3) Students expressed a high level of satisfaction with the Thai reading lesson plan using gamification-based learning combined with Citta Bhāvanā, with an overall average score of 2.67, interpreted as a high level of satisfaction.